Religious Content in Anime â€œEnen no Shouboutaiâ€ - Janto, Dina Dharma; Ong, Susy (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2021)
As more and more religious content appears in anime, the actual meaning of its use in anime may be different. This phenomenon is known as religious cosmetics introduced by Jolyon Baraka Thomas. Religious cosmetics introduces the term religious vocabulary and religious imagery. This study focuses on analyzing religious vocabulary, and aims to prove whether the Shinto religious vocabularies that appears in the anime Enen no Shouboutai season 1 (2019) are religious cosmetics. The method used in this study is qualitative descriptive. The use of words in the anime Enen no Shouboutaiseason 1 will be compared with the meaning of the vocabulary from the Shinto religious dictionary compiled by Brian Bocking. The results showed that there are eighteen data of religious vocabularies that appear in anime Enen no Shouboutai season 1, which can be divided into five categories, namely (1) ‘amaterasu’, (2) ‘kami’, (3) ‘matsuri’, (4) ‘oni’, and (5) ‘sake’. However, among those five categories appeared throughout the series, four were found as Shinto religious vocabularies which used as religious cosmetics while one category (3) ‘matsuri’ was not used as religious cosmetics. The reason is because the meaning and the use of the word is getting wider, not only used in Shinto related topics, but also in daily life generally.